Reshaping criminology with AI - Ortiz-Rodriguez, Fernando; Shandilya, Shishir K.; Vargas Orozco, Cynthia; Ibarra Costilla, Juana; Llamas Covarrubias, Jersain (Premier research source, 2026)
"This book aims to collect new insights and research on digital criminology and their use of technology aid. The new paradigm of crime is digital. The future of cybersecurity rests on a synergistic partnership between AI and human expertise, combining their strengths for more effective defense against evolving cyber threats"-- Provided by publisher